2014
DOI: 10.1155/2014/570420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poria cocos on Puromycin Aminonucleoside‐Induced Nephrotic Syndrome in Rats

Abstract: Nephrotic syndrome is associated with altered renal handling of water and sodium and changes in the levels of aquaporins (AQPs) and epithelial Na channels (ENaCs). The dried sclerotia of Poria cocos Wolf (WPC) have been used for treating chronic edema and nephrosis. We evaluated the effects of WPC on puromycin aminonucleoside- (PAN-) induced renal functional derangement and altered renal AQP2 and ENaC expression. In the nephrotic syndrome rat model, animals were injected with 75 mg/kg PAN and then treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…47 The water extract of poria cocos can reduce blood uric acid levels in rats, and at the same time can reduce the creatinine level to protect the kidney. 48 Plantago seed extract affects the activity of xanthine oxidase in the liver of model rats, can prevent kidney damage, and reduce inflammation. 49 In the clinical study, we treated 105 gout patients with allopurinol and Tongbixiao pills to demonstrate the efficacy of Tongbixiao pills for gout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 The water extract of poria cocos can reduce blood uric acid levels in rats, and at the same time can reduce the creatinine level to protect the kidney. 48 Plantago seed extract affects the activity of xanthine oxidase in the liver of model rats, can prevent kidney damage, and reduce inflammation. 49 In the clinical study, we treated 105 gout patients with allopurinol and Tongbixiao pills to demonstrate the efficacy of Tongbixiao pills for gout.…”
Section: Discussionmentioning
confidence: 99%
“…47 The water extract of poria cocos can reduce blood uric acid levels in rats, and at the same time can reduce the creatinine level to protect the kidney. 48 Plantago seed extract affects the activity of xanthine oxidase in the liver of model rats, can prevent kidney damage, and reduce inflammation. 49…”
Section: Discussionmentioning
confidence: 99%
“…One of these preparation, Wulinsan, was shown to confer a significant renoprotective effect (Yang et al, ; Yoon et al, ) and is widely used in the treatment of patients with CKD. A number of studies have demonstrated the renoprotective effect of P. cocos (Lee et al, ; Yoon et al, ; Lee et al, ). In addition, several studies have shown the protective effect of lanostane triterpenoids derived from the sclerotia of P. cocos on renal tubular epithelial cells including LLC‐PK1 and HK‐2 cells (Lee et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the ADR-induced NS rat model, Poria extract could significantly improve the levels of urine protein, creatinine, serum total cholesterol, and IL-4 cytokine and attenuate kidney injury ( Zan et al, 2017 ). Likewise, Poria treatment significantly improves the disturbance of water metabolism in puromycin aminonucleoside (PAN)-induced NS rats by inhibiting the expression of the epithelial sodium channel and AQP2 ( Lee et al, 2014 ). An in vitro study also revealed that Poria treatment inhibited the activation of Sgk1 and decreased the expression of TonEBP mRNA ( Lee et al, 2012 ).…”
Section: Tcm For Treating Ckdmentioning
confidence: 99%